Law Enforcement Of Criminal Acts Of Dissemination Of Population Document Data By Dinas Dukcapil Kab. Mukomuko (Study Of Mukomuko District Police Legal Area - Juliantio Dwi Pramana; Mikho Ardinata; Ahmad Dasan; Rangga Jayanuarto (JURNAL HUKUM SEHASEN, 2024)
The majority of people do not know that the importance of personal identity in the law and that there are many things that a person can do using one's personal identity, and can lead to unlawful acts, thus causing people who are unfamiliar with this law to suffer losses due to some individuals who are irresponsible in bringing order. Population administration in areas specifically in Bengkulu Province, Mukomuko Regency. This research method is Empirical Legal Research, with data sources obtained through interviews with the Mukomuko Police. The research results show that law enforcement regarding the dissemination of population data is regulated in the Population Administration Law. The process includes investigation, arrest and trial with the principles of justice. Protection of data confidentiality is strictly regulated, important for maintaining individual privacy and public trust. The obstacles to law enforcement include lack of public awareness, technical obstacles, and limited resources. Collaborative efforts from the government, law enforcement agencies and the community are needed to increase awareness, resources and technology to overcome these obstacles.